Image Processing For Uav Autonomous Navigation - Klouda, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
The project deals with image recognition, which is provided by a camera and microcomputer. The program is written in Python and based on a comparison with the predefined Haar cascade, recognizes the object on the poly-camera's visual field and borders it. From the position and size of this object, the microcomputer sends commands to the flight controller and the drone is controlled through the camera.
Keywords: UAV; recognize; drone; Python; autonomous navigation